2014
DOI: 10.1177/1071100714555712
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of Distal Fibula Fractures

Abstract: Level of Evidence:Level V, expert opinion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…A 1-mm displaced talus is associated with more than 40% of tibiotalar contact area decreases and changes [5]. The lateral malleolus is important for ankle mortise stability, especially in AO (Arbeitsgemeinschaft für Osteosynthesefragen )/OTA (Orthopaedic Trauma Association )-44B transsyndesmotic fibula fractures accompanied by mortise changes and talus tilt [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A 1-mm displaced talus is associated with more than 40% of tibiotalar contact area decreases and changes [5]. The lateral malleolus is important for ankle mortise stability, especially in AO (Arbeitsgemeinschaft für Osteosynthesefragen )/OTA (Orthopaedic Trauma Association )-44B transsyndesmotic fibula fractures accompanied by mortise changes and talus tilt [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, both groups demonstrated a relatively low complication rate (10%), with hardware-related issues being the most prevalent. The rate of hardware removal is similar to other procedures, [6][7][8][9][10][11] such as anterior cruciate ligament (ACL) reconstructions, where screws or staple prongs are commonly proud or unicortical due to the nature of this type of hardware. [12][13][14] Hardware function (such as in ACL graft tunnel mismatch) must be considered, because repositioning of the hardware placed around an already well-secured surgical site or ACL graft could lead to significant graft damage.…”
Section: See Related Article On Page 2141mentioning
confidence: 85%
“…11 This rate is significantly higher in certain high-risk patients such as patients over 65 years of age with poor soft tissue, diabetics, and smokers. 13 Several studies reviewing intramedullary fixation of fibular fractures have reported significantly lower rates of wound breakdown and hardware irritation than seen traditionally with standard AO techniques. 2,5,8,10,12,14,15 The majority of complications seen in early descriptions of the procedure were minimized as the technique evolved.…”
Section: Discussionmentioning
confidence: 99%
“…17 Regardless of fracture pattern, these devices are most commonly used in elderly patients with osteoporotic bone, and patients who are at high risk for hardware failure or skin and soft tissue complications, including diabetic patients and smokers. 13…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation